HARMONIZING EDUCATION AND SHARIA: TINGKILAN MUSIC AS A MEDIUM FOR INTERNALIZING KI HADJAR DEWANTARA’S EDUCATIONAL PHILOSOPHY AMONG URBAN MUSLIMS - Meita Setyawati; Indar Sabri; Setyo Yanuartuti; Arif Hidajad; Syaiful Arifin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2026)
This study examines Tingkilan music as a cultural medium that bridges Ki Hadjar Dewantara’s educational philosophy with the principles of Islamic law in shaping the moral and cultural character of urban Muslim communities. Originating from the Kutai people of East Kalimantan, Tingkilan music has long functioned not merely as artistic expression but also as a vehicle for transmitting ethical, social, and spiritual values rooted in Islamic teachings and local wisdom. In contemporary urban contexts—where Muslims increasingly seek to balance religious commitment with cultural identity—Tingkilan offers a meaningful and culturally grounded alternative. Employing a descriptive qualitative approach, this research draws upon literature analysis and in-depth interviews with local artists and cultural figures engaged in the preservation and performance of Tingkilan. The data were analyzed by correlating the aesthetic and moral dimensions of Tingkilan music with the frameworks of maqāṣid al-sharī‘ah and fiqh al-ḥaḍārah, both of which emphasize the adaptability of Islamic law within dynamic cultural and social contexts. The findings demonstrate a strong convergence between the values of creativity (cipta), sensibility (rasa), and intentionality (karsa) articulated by Ki Hadjar Dewantara and the objectives of Islamic law, particularly in promoting public welfare (al-maṣlaḥah), preserving human dignity (ḥifẓ al-‘irḍ), and fostering social harmony. Through its poetic lyrics and musical form, Tingkilan functions as a form of cultural da‘wah, conveying Islamic moral messages in a subtle yet aesthetic manner that enhances their accessibility among urban Muslim audiences. This study suggests that traditional Islamic arts such as Tingkilan can play a strategic role in character education, cultural preservation, and the promotion of moderate religious engagement. Accordingly, Tingkilan music represents a practical model for harmonizing education, sharia, and local culture within contemporary Indonesian Muslim society.